Perbandingan Hasil Belajar Matematika Siswa Melalui Metode Pembelajaran Kooperatif Tipe Jigsaw dengan Strategy Genius Learning - Nur Furqan Ahmad Hasan; Hamzah Upu; Rosidah (LPPM Universitas Terbuka, 2023)
This study aims to determine whether there is a significant difference in the application of jigsaw type cooperative learning method with genius learning strategy on mathematics learning outcomes of fifth grade students of SD Negeri Biringkaloro Pallangga. Pseudo-experimental research method. Research design pretest-posttest comparison group design. The study population was all fifth grade students of SD Negeri Biringkaloro Pallangga totaling 160 students. The research sample amounted to 80 students obtained using simple random sampling. Data collection techniques using learning outcomes test instruments and observation sheets. Data analysis techniques using descriptive statistical analysis and inferential statistics. The results of descriptive statistical analysis obtained the average mathematics learning outcomes of students with jigsaw type cooperative method 74.00 and genius learning strategy 76.88. The results of inferential statistical analysis showed that the sign value obtained was 0.000 in the sense that (0.000 <0.05) so that it was concluded that there was a significant difference in mathematics learning outcomes by applying the jigsaw type cooperative method and the genius learning strategy in fifth grade students of Biringkaloro Pallangga State Elementary School. The conclusion of the study shows that the application of the jigsaw type cooperative learning method with the genius learning strategy is very influential on students' mathematics learning outcomes, especially students' ability to solve math problems easily and quickly.